CHARACTERISTICS OF LIPID PROFILES ANALYSIS IN A PUBLIC HOSPITAL PRACTICE IN NORTHEASTERN NIGERIA. - DS MSHELIA; W GASHAU (Ntec Specialist, 2001)
Background: Northeastern Nigeria is peculiar concerning lipid metabolism due to sizeable multiethnic population, common practice of consanguineous marriages, and high intake of animal fats (mai shanu). Therefore, rational requests and interpretation of results in the diagnosis of dyslipidaemia is very important in this part of the country. In spite of these seemingly obvious predisposing factors of dyslipidaemia, little, if any, report at all on hyperlipidaemia in this region has been documented. Objectives: This retrospective study intends to shed light on the characteristics of requests for lipid analysis, the subjects with hypercholesterolaemia and their lipid profile results when available. Methods: The clinical records of 328 (29.5%) out of 1110 patient requests received in the University of Maiduguri Teaching Hospital Laboratory with hypercholesterolaemia over a period of three years (1998-2000) were retrieved and analyzed. Results: There was a slight male preponderance 179 54.6%) over females 149(45.4%) with a ratio of 1.2:1. Hypercholesterolaemia in particular was poorly investigated as the primary cause was not sought in 40(12.2%) cases, 24(7.3%) discovered on routine checkup were not investigated further, and only 19(5.8%) of 176 cases with moderate to severe levels had lipid profile, of which 4(1.2%) alone had HDL-Cholesterol done together with total cholesterol at first request. Hypercholesterolaemia in this environment was most commonly associated with cardiovascular diseases and diabetes mellitus with or without hypertension. Factors such as alcohol intake, cigarette smoking and thiazide diuretic use were not significant causes of hypercholesterolaemia. Conclusion: Documentation/requests for lipid investigations were incomplete. The need for estimating both total cholesterol and HDL-Cholesterol on first request and their ratio determined alongside Body Mass Index (BMI) is emphasized as a standard routine especially in hypertension with or without diabetes mellitus, cererovascular diseases/stroke and obesity